Magnetofluorescent micellar complexes of terbium(iii) as potential bimodal contrast agents for magnetic resonance and optical imaging1. Issue 14 (18th February 2015) - Harris, Michael; Carron, Sophie; Vander Elst, Luce; Laurent, Sophie; Muller, Robert N.; Parac-Vogt, Tatjana N.
<x xml:space="preserve">Abstract</x> Micellar nano-aggregates containing Tb(iii) have been evaluated as a single lanthanide bimodal contrast agent for magnetic resonance and optical imaging.